2013
DOI: 10.1152/ajpendo.00630.2012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of adipose branched-chain amino acid catabolism enzyme expression and cross-adipose amino acid flux in human obesity

Abstract: Elevated blood branched-chain amino acids (BCAA) are often associated with insulin resistance and type 2 diabetes, which might result from a reduced cellular utilization and/or incomplete BCAA oxidation. White adipose tissue (WAT) has become appreciated as a potential player in whole body BCAA metabolism. We tested if expression of the mitochondrial BCAA oxidation checkpoint, branched-chain ␣-ketoacid dehydrogenase (BCKD) complex, is reduced in obese WAT and regulated by metabolic signals. WAT BCKD protein (E1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

23
278
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(303 citation statements)
references
References 53 publications
23
278
0
2
Order By: Relevance
“…Thus, our and previous studies suggest that adipose tissue may play an important role in the increased circulating BCAA levels in T2DM. Interestingly, in our study, the downregulation of BCAA degradation genes was more pronounced in omental adipose tissue compared with subcutaneous adipose tissue (18) (Supplementary Table 7), which is in agreement with a more pronounced role for omental adipose tissue in the control of metabolic health (9). Surprisingly, we did not find correlation between expression levels of genes involved in BCAA metabolism and BCAA serum levels (data not shown).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, our and previous studies suggest that adipose tissue may play an important role in the increased circulating BCAA levels in T2DM. Interestingly, in our study, the downregulation of BCAA degradation genes was more pronounced in omental adipose tissue compared with subcutaneous adipose tissue (18) (Supplementary Table 7), which is in agreement with a more pronounced role for omental adipose tissue in the control of metabolic health (9). Surprisingly, we did not find correlation between expression levels of genes involved in BCAA metabolism and BCAA serum levels (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…Increased protein consumption containing these essential amino acids may raise their plasma levels, but some data suggest that protein intake and circulating BCAA levels are not necessarily correlated (16,17). Alternatively, downregulation of catabolic enzymes in adipose or other tissues might be involved (8,9). In a parallel study, we analyzed the transcriptome in visceral and subcutaneous adipose tissue samples by RNA sequencing in the cohort of the current study (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss-of-function mutations in PPM1K in humans [21], and disruption of key BCAA metabolism in obese mice and Zucker rats, exhibit a reduced expression of the mitochondrial isoform of branched chain-amino-acid transaminase (BCAT2; which catalyses the first and reversible step in BCAA catabolism), and mitochondrial branched chain α-keto acid dehydrogenase (BCKD) complex E1-α (which catalyses the rate-controlling and the first irreversible step), leading to increased plasma BCAA levels [22,23]. A decreased BCAA metabolism in fat tissue may contribute to higher BCAA levels in individuals with insulin-resistant obesity [2,[22][23][24]. Intriguingly, a recent study also showed that the gut microbiota can contribute to elevated BCAA levels in insulin-resistant states [25].…”
Section: Discussionmentioning
confidence: 99%
“…PD and BCKD are closely related enzyme complexes (38) present in a number of metabolically active tissues (e.g., muscle, liver, and adipose); they are regulated by a number of common factors, including insulin. It is possible that they both play a role in affecting plasma a-HB and a-KB levels, although their relative activities and tissue specificities may well differ in iIFG and iIGT.…”
Section: Discussionmentioning
confidence: 99%